PENGARUH SOCIAL MEDIA MARKETING DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KPR NON SUBSIDI DENGAN MEDIASI PERSEPSI MEREK (STUDI PADA BANK XYZ) - Piramita, Santi; Hannan, Sufrin; Purba, Jan Horas Vervady (Jurnal Aplikasi Bisnis dan Manajemen, 2021)
The purpose of this research is how to social media marketing and service quality to impact non-subsidized mortgage purchasing decisions, with brand perception as a mediating variable. The model in this research was designed using hierarchical components with a reflective-reflective measurement model consisting of four variables (social media marketing, service quality, brand perception and purchase decisions) and sixteen dimention (entertainment, informative, interactive, tangible, reliable, responsiveness, assurance, empathy, brand experience, brand affective, brand trust, recognition of needs, information search, evaluation of alternatives, purchase decisions and post-purchasing behavior). Data analysis in this research was using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The results revealed that social media marketing factors and service quality have a positive and significant effect on brand perception. In addition, social media marketing factors and brand perceptions were found to have a positive and significant effect on purchasing decisions and service quality factors which had an insignificant effect. The mediating role of brand perception was found to have a partial mediating effect on the relationship between social media marketing and purchasing decisions, while the relationship between service quality was found to be fully mediated. Keywords: purchase decision, service quality, brand perception, social media marketing, non subsidized mortgage